Dysphagia in multiple sclerosis: pathophysiology, assessment, and management—an overview - Restivo, Domenico A.; Quartarone, Angelo; Bruschetta, Antongiulio; Alito, Angelo; Milardi, Demetrio; Marchese-Ragona, Rosario; Iezzi, Ennio; Peter, Sheila; Centonze, Diego; Stampanoni Bassi, Mario (Frontiers in Neurology, 2024)
Dysphagia is a frequent and life-threatening complication of multiple sclerosis (MS). Swallowing disturbances may be present at all stages of MS, although their prevalence increases with age, with disease duration, and in progressive phenotypes. The pathophysiology of dysphagia in MS is likely due to a combination of factors, including the involvement of corticobulbar tracts, the cerebellum, and the brainstem. Accurate diagnosis and early management of swallowing disorders improve quality of life and may delay complications or invasive therapeutic interventions. Here we provide an overview of the pathophysiology, the assessment, and the management of MS dysphagia, also examining the possible role of novel therapeutic strategies. Although studies using imaging and neurophysiological techniques have contributed to better characterize swallowing alterations in MS, the treatment of dysphagia is still challenging. Rehabilitation represents the main therapeutic approach for swallowing disorders. Recently, some innovative neurophysiological approaches, such as pharyngeal electrical stimulation (PES), repetitive transcranial magnetic stimulation (rTMS), and transcranial direct current stimulation (tDCS), have been proposed as a supplement to swallowing therapy in different neurological conditions. However, only few studies have explored the role of neuromodulation for MS dysphagia.